A quantitative examination of crime: Reported incidents at land-grant higher education institutions versus reported societal incidents - Doss, Daniel A.; Lackey, Hilliard; McElreath, David; Goza, Rebecca; Gokaraju, Balakrishna; Tesiero, Raymond; Sheffield, Jeremy (Journal of Interdisciplinary Studies in Education, 2017)
This study investigates differences in reported criminality between land-grant higher education institutions and society for the period encompassing 2001-2010. Using analysis of variance (ANOVA) and a stratification of reported incidents of campus crime (per the Clery Act) versus societal crime, statistically significant outcomes were observed for the crime categories of cumulative crime, robbery, sex crimes, assault crimes, burglary, and motor vehicle theft. Within the contexts of campus safety and campus security, the outcomes of this study reiterate the uniqueness of campus criminality among land-grant higher education settings.